The influence of Arabic media coverage on the formation of public opinion - Said, Marwa (Opción, 2019)
The purpose of this study was to identify the media content of Syrian TV channels which support and against the Syrian regime in addition to the political opinion of viewers who watch such channels via the descriptive research methodology. The results showed there is no statistical significance in forming the political opinion about the Syrian crisis due to the demographic as well as personal variables. In conclusion, frequent viewers, who believe that such channel programs convey valid different crisis details, are influenced by watching such TV channels clearly.